PENGARUH MODEL ACTIVE LEARNING BERBANTU MEDIA ANIMASI TERHADAP KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK - Indah Nor Inayah; Nurul Septiana; Nanik Lestariningsih (Pedagogi Hayati, 2018)
ABSTRACT. This study aims to determine the effect of Active Learning model on the liveliness and learning outcomes of syudents in class XII MIPA MAN Kota Palangka Raya material cell division. Active Learning is a learning that can encourage avtive learners to ask and argue. Activeness is needed in learning activities because of the participation of the deeper undedrstanding. Observations and interviews with teacher of MAN Kota Palangka Raya obtained information that learners tend to be passive and replication value of cell division material under KKM. The situation is deemed necessary to be by applying the Active Learning model to determine its influence on the liveliness and learning outcomes. The sample was taken using puposive sampling technique. Based on the results of this study note that the Active Learning model can increase the liveliness of learners with the percentage of 84,90%in the experimental class and 58,85% in the control class. This model also affect the increase of students’ learning outcomes with average N-gain in the experimental class of 0,70 which is high while the control class is 0,44 whichis claaified as N-gain is. The conclusion of this research is the influence of Active Learning on the activity and learning outcomes of students of class XII MIPA MAN Kota Palangka Raya material of cell divisoin. ABSTRAK. Penelitian ini bertujuan untuk mengetahui pengaruh model Active Learning terhadap keaktifan dan hasil belajar peserta didik kelas XII MIPA MAN Kota Palangka Raya materi pembelahan sel. Active Learning merupakan pembelajaran yang dapat memacu peserta didik aktif bertanya dan berpendapat. Keaktifan sangat diperlukan dalam kegiatan pembelajaran karena dengan adanya partisipasi maka pemahaman lebih mendalam. Hasil observasi dan wawancara dengan guru MAN Kota Palangka Raya diperoleh informasi bahwa peserta didik cenderung pasif dan nilai ulangan materi pembelahan sel dibawah KKM. Keadaan tersebut dirasa perlu diselesaikan dengan menerapkan model Active Learning untuk mengetahui pengaruhnya terhadap keaktifan dan hasil belajar. Sampel diambil menggunakan teknik purposive sampling. Berdasarkan hasil penelitian tersebut diketahui bahwa model Active Learning dapat meningkatkan keaktifan peserta didik dengan persentase 84,90% dikelas eksperimen dan 58,85% dikelas kontrol. Model ini pun berpengaruh terhadap meningkatnya hasil belajar peserta didik dengan rata-rata N-gain dikelas eksperimen sebesar 0,70 yang tergolong tinggi sedangkan dikelas kontrol sebesar 0,44 yang tergolong N-gain sedang. Kesimpulan penelitian ini adalah adanya pengaruh model Active Learning terhadap keaktifan dan hasil belajar peserta didik kelas XII MIPA MAN Kota Palangka Raya materi pembelahan sel.